Rehabilitation for students diagnosed with depression and/or anxiety disorder - feasibility and perceived impact of OPI group rehabilitation program in Finland - Schmidlechner, Kaija Appelqvist (International Journal of Psychosocial Rehabilitation, 2015)
The OPI mental health rehabilitation program is a new form of outpatient group rehabilitation for adolescents and young adults aged 16−25 years studying in vocational schools and diagnosed with mood or anxiety disorders. This study aimed at investigating the feasibility and perceived impact of the program on participants’ learning and func- tional capacities, quality of life and severity of depression.The data (n=70) were collected using questionnaires and with focus group interviews. Quality of life was measured with the Eurohis-8 scale, severity of depression with RBDI.Quality of life and learning capacities were increased and severity of depression was reduced among participants during the rehabilitation. Positive outcomes were associated with timely occurrence of the rehabilitation, co-opera- tion with the mental health service responsible for the treatment during the program and with well-functioning inter- action between client and counsellor. Peer support was experienced as the most remarkable benefit of the program among participants